East meets West: Mounted Encounters in Early and High Mediaeval Europe - Gassmann Jürg (Acta Periodica Duellatorum)
By the Late Middle Ages, mounted troops - cavalry in the form of knights - are established as the dominant battlefield arm in North-Western Europe. This paper considers the development of cavalry after the Germanic Barbarian Successor Kingdoms such as the Visigoths in Spain or the Carolingian Franks emerged from Roman Late Antiquity and their encounters with Islam, as with the Moors in Iberia or the Saracens (Arabs and Turks) during the Crusades, since an important part of literature ascribes advances in European horse breeding and horsemanship to Arab influence. Special attention is paid to information about horse types or breeds, conformation, tactics - fighting with lance and bow - and training. Genetic studies and the archaeological record are incorporated to test the literary tradition.